Breaking Barriers to Adoption: A Multi-Stakeholder Platform Approach to Promoting Improved Common Bean Varieties among Farmers in Malawi - Kadakoma Rambiki, Ivy; Magreta, Ruth; Phiri, Alexander; Birachi, Eliud Abucheli; Larochelle, Catherine; Mutua, Mercy Muli; Rubyogo, Jean Claude; Nkhata, Wilson (2024)
The study’s data is from a survey that was conducted to address the objective of transforming seed systems to respond to common bean varieties through multi-stakeholder platforms in the Malawi (MSP) project. The output of the project hypothesis was evidence that using the Multi-stakeholder Platform (MSP)-based Participatory Variety Evaluation (PVE) approaches increases awareness and accelerates uptake of new market-demanded varieties. The study's main objective was to assess the influence of multi-stakeholder platforms (MSPs) and farmers' attitudes on the uptake of improved common bean varieties. The survey was conducted in Dedza, Mzimba, and Kasungu districts of Malawi, which are among those areas where common bean is mostly cultivated by farmers due to the soil type, climate, and rainfall pattern. According to the MSP project, Dedza district, which is in the central region, and Mzimba district, in the northern region of Malawi, were the intervention areas. Whereas Kasungu district, which is in the central region and also borders Mzimba district, is the counterfactual site. Metodology:The study used a multi-staged sampling procedure where, in the first stage, purposive sampling was used to select districts and Extension Planning Areas (EPAs) within each district. Then, sections, villages, and farmer households were selected randomly. The information was collected at the household level, with the principal decision maker in a household responding to the full survey. The study managed to collect data from 797 farmer households, of which 62% were collected from intervention areas and 38% were collected from counterfactual areas.